Numerical study of adaptive grids for laminar flow in a suddenly expanding channel - Kholboev, Bakhodir Murodovich; Asrakulova, Dono Sunnatullaevna; Engalicheva, Nelia Rustamovna; Madaliev, Murodil Erkinjon ugli; Mirzoev, Akmal Ahadovich (Zielona Góra: Uniwersytet Zielonogórski)
In this article, a numerical study was carried out to study the dynamic adaptive grid method, based on the concept of the equidistribution method. The article explores a method for adapting the computational grid to solving two-dimensional Navier-Stokes differential equations, which describe the physical processes of gas dynamics specifically for the problem of a two-dimensional channel with an expansion coefficient (H/h) = 2.
Keywords: Navier-Stokes equations; dynamic adaptive grid; separated flow; control volume method; flat channel with reverse ledge